2022
DOI: 10.1002/adfm.202203866
|View full text |Cite
|
Sign up to set email alerts
|

Room‐Temperature Colossal Elastocaloric Effects in Three‐Dimensional Graphene Architectures: An Atomistic Study

Abstract: Solid‐state cooling exploits the thermal response of caloric materials when subjected to external physical fields and represents a promising alternative to conventional refrigeration technologies. However, existing caloric materials are often limited by relatively small caloric response and hysteresis issues rooted in first‐order structural transitions. Here, colossal and reversible elastocaloric effects near room temperature in superelastic graphene architectures are predicted by thermodynamic analysis and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 116 publications
1
34
0
Order By: Relevance
“…Previous researches have shown that the construction of covalently bonded SWCNT based hybrid materials can enhance their mechanical stability. 13,14 Besides, lots of previous studies have attempted to encapsulate a variety of materials into the inner space, such as carbon nanomaterials, 15,16 organic molecules, 17,18 etc., 19 to improve the properties of carbon nanotubes. One typical approach is the encapsulation of fullerenes into SWCNTs, forming a carbon peapod structure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches have shown that the construction of covalently bonded SWCNT based hybrid materials can enhance their mechanical stability. 13,14 Besides, lots of previous studies have attempted to encapsulate a variety of materials into the inner space, such as carbon nanomaterials, 15,16 organic molecules, 17,18 etc., 19 to improve the properties of carbon nanotubes. One typical approach is the encapsulation of fullerenes into SWCNTs, forming a carbon peapod structure.…”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, various derived carbon materials, such as graphitic carbon, graphite-diamond, and amorphous diamond, are produced experimentally by varying temperature and pressure. 13–15…”
Section: Introductionmentioning
confidence: 99%
“…A temperature change induced by external strain, known as the elastocaloric effect (ECE), has great potential for next-generation thermal management technologies due to its environmental friendliness and economic benefits. To make this technology more efficient, efforts have been made to find highly efficient elastocaloric materials. In particular, in view of the growing interest in miniaturized refrigeration, at the nanoscale, the study of the ECE in nanostructures has already begun. …”
mentioning
confidence: 99%
“…To investigate the ECE in a model GK lattice at the atomic scale, we used the LAMMPS code with the adaptive intermolecular reactive empirical bond order (AIREBO) potential in reactive MD simulations. This potential accurately addresses carbon-based nanostructures and provides reliable potential energy values to study their mechanical and thermal properties. , Besides, the LAMMPS/AIREBO methodology has been successfully used to describe the ECE in carbon nanomaterials. ,,,, The GK model used in this study is shown in Figure and has the following properties: l 0 = 332 Å, l 1 = 48 Å, l 2 = 4.8 Å, h 0 = 100 Å, h 1 = 68 Å, h 2 = 35 Å, d f = 19 Å, 12 012 carbon atoms and 1244 hydrogen atoms.…”
mentioning
confidence: 99%